ISU ReD: Research and eData 2021
DOI: 10.30707/fpbiosci/nivs7941
|View full text |Cite
|
Sign up to set email alerts
|

Dataset for Response of the Invasive Alliaria Petiolata to Extreme Temperatures and Drought

Abstract: Data is used to generate Fig. S1, which includes densities of rosettes and mature plants from 2004-2014 /*Data are rosettes, plotid (plot identification), counts, and quadrats. There are two woods each with two blocks. Quadno are quadrat numbers, numbers 1-11 indicate sample years from 2004-2014. Codes are SAS for PROC GLIMMIX.*/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Interestingly, second-year garlic mustard plants are also an important competitor with the first-year rosettes; intraspecific competition is likely the cause of alternating dominance between the two cohorts (Bauer et al 2010 , Davis et al 2012 ), creating a strong biennial pattern at most sites (Pardini et al 2009 ). However, extreme climate events can disrupt this alternating pattern by reducing the abundance of garlic mustard rosettes (Anderson et al 2021 ). Overall, studies of garlic mustard interactions with native plants show that garlic mustard is not gaining an advantage over native species through direct, strong competition for resources.…”
Section: Mechanisms For Garlic Mustard Invasion Success Across Ecolog...mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, second-year garlic mustard plants are also an important competitor with the first-year rosettes; intraspecific competition is likely the cause of alternating dominance between the two cohorts (Bauer et al 2010 , Davis et al 2012 ), creating a strong biennial pattern at most sites (Pardini et al 2009 ). However, extreme climate events can disrupt this alternating pattern by reducing the abundance of garlic mustard rosettes (Anderson et al 2021 ). Overall, studies of garlic mustard interactions with native plants show that garlic mustard is not gaining an advantage over native species through direct, strong competition for resources.…”
Section: Mechanisms For Garlic Mustard Invasion Success Across Ecolog...mentioning
confidence: 99%
“…Only 2 of the 12 regional (more than three state) studies since 2008 incorporated data collected over a decadal time scale (Averill et al 2018 , Blossey et al 2021 ), with 2 others using herbarium specimens to estimate invasion processes over regional scales over up to two centuries (Lankau et al 2009 , Clark et al 2018 ). Bialic-Murphy and colleagues ( 2020 ) used 6 years of detailed demographic data at a single site to find that garlic mustard's impact differed greatly over time and other studies have found dramatic decreases (Lankau 2012b , Murphy and McCarthy 2014 , Nuzzo et al 2017 , Faison et al 2019 , Anderson et al 2021 , Blossey et al 2021 ) or increases (Rooney and Rogers 2011 ) in garlic mustard abundance over years to decades. These findings indicate that annual and short-term studies are poor representatives of future dynamics and point to the strong need for longitudinal studies of garlic mustard invasion (Lankau et al 2009 , Blossey et al 2021 ).…”
Section: How and Where Has Garlic Mustard Been Studied?mentioning
confidence: 99%
See 1 more Smart Citation